MANAJEMEN PENGANGKUTAN BARANG KIMIA BERBAHAYA: TINJAUAN KESELAMATAN DAN PEMENUHAN REGULASI - Syaiful Barkah; Alugoro Mulyowahyudi (LPPM Sekolah Tinggi Ilmu Ekonomi PGRI Sukabumi, 2020)
This study analyzes the safety management of transporting dangerous chemical goods that are transported from the factory to the customer. By conducting a risk assessment of transportation activities and reviewing company compliance with regulations and laws. This research is descriptive qualitative or observational, the analytical method used in this study is the HIRADC (Hazard Identification Detemining Control Risk Assessment) method. The results of this study provide an overview of the level of safety of transporting hazardous chemicals to carry out risk assessments in shipping goods to customers. Risks that score more than 1 are risks that must be followed up by making an objective program. The level of risk comes from a combination of likelihood (probability) and severity of impact (consequences). The results of this study are expected to be used to control and reduce current risks. Evaluation of company compliance with government regulations and legislation, can be used as a basis for developing compliance plans that were not previously met.